Nutritional status and dietary intake of the orphans: A case study in the ICH (Intervida Children Home) in Dhaka city in Bangladesh (Bangladesh Journal of Nutrition, 2013)
The study was conducted among Intervida beneficiaries (Students) on October 2010. Total number of students was 46. The purpose of the study was to assess the nutritional status and dietary intake of the orphan children. All of the children were abandoned and got admitted to the ICH within one year of age. Among them 89.1% were Muslim, 2.2% were Christian and 8.7% were Hindu. 8.70 % students got enrolled in special education as they were either physically or mentally disabled. The mean±Sd of age, height and weight were 104.65±16.51 months, 126.37±6.98cm and 26.87±6.98kg respectively. While BMI was considered, it was found that 60.87% (28) students were normal, 21.74% (10) student were overweight, 6.5% (3) students were and 10.87% (5) students were underweight. Considering HAZ (Height for age Z-score), 89.1% (41) were normal, 8.7% (4) Stunted and 2.2% (1) tall. While WAZ (Weight for age Z-score) was considered, 84.8% (39) were normal, 2.2% (1) was overweight and 13% (6) were underweight. On the other hand, when, WHZ(Weight for Height Z-score) was used, it was found that 83.8% (31) students were normal, 8.1% (3) student were overweight , 5.4% (2) students were obese and 2.7% (1) student was Wasted. The mean calorie, protein, carbohydrate and fat intake were 2270 kcal, 65 gram, 335 gram and 73 gram respectively. Carbohydrate, protein and fat provided 59%, 12% and 29% of total calorie respectively. Average intake of calcium, iron, vitamin A, carotene, vitamin B1, vitamin B2, niacin, vitamin C and zinc intake was 826 mg, 31 mg, 6462 IU, 10508 ?g, 1.60 mg , 1.64 mg, 19 mg , 111 mg and 10.2 mg respectively. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14034 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.23-30